Foster to Receive ACM-IEEE Award. (Communications of the ACM, 2022)
The article announces that Argonne National Laboratory Division Director Ian Foster is expected to receive the 2022 ACM-IEEE CS Ken Kennedy Award for his work with distributed computing, computer programming methods, and grid computing involving the remote and coordinated use of computers.